2007
DOI: 10.1016/j.watres.2007.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and complete destruction of perchlorate in water and ion-exchange brine using stabilized zero-valent iron nanoparticles

Abstract: Because of the unique chemistry of perchlorate, it has been challenging to destroy perchlorate. This study tested the feasibility of using a new class of stabilized zero-valent iron (ZVI) nanoparticles for complete transformation of perchlorate in water or ionexchange brine. Batch kinetic tests showed that at an iron dosage of 1.8 g L À1 and at moderately elevated temperatures (90-95 1C), $90% of perchlorate in both fresh water and a simulated ion-exchange brine (NaCl ¼ 6% (w/w)) was destroyed within 7 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(72 citation statements)
references
References 38 publications
3
66
0
1
Order By: Relevance
“…In recent years, nZVI has attracted the attention of many scientists (19). Due to high reduction capacity, high efficiency, abundance, cheapness, and its unique atomic, molecular, and chemical properties, nZVI has been used in the treatment of nitrate contaminated water (20,21). Despite numerous benefits of this technology, there are limitations in the use of nZVI such as pH control, ammonium production, and particle aggregation (20,22).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nZVI has attracted the attention of many scientists (19). Due to high reduction capacity, high efficiency, abundance, cheapness, and its unique atomic, molecular, and chemical properties, nZVI has been used in the treatment of nitrate contaminated water (20,21). Despite numerous benefits of this technology, there are limitations in the use of nZVI such as pH control, ammonium production, and particle aggregation (20,22).…”
Section: Introductionmentioning
confidence: 99%
“…As a strong reductant, Fe 0 nanoparticles can degrade a wide range of pollutants by adsorption and chemical reduction. Fe 0 nanoparticles has been successfully used for the treatment of chlorinated hydrocarbons (Lien and Zhang 2005;Liu et al 2005), polychlorinated biphenyls (Varanasi et al 2007), organochlorine pesticides (Elliott et al 2009), and inorganic pollutants such as perchlorate (Xiong et al 2007), chromate (Xu and Zhao 2007;Franco et al 2009), nitrate (Liou et al 2005), arsenic (Morgada et al 2009), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior TEM images (He et al 2007;Xiong et al 2007) indicated that the CMC-stabilized nanoparticles appeared as well-dispersed, discrete nanoscale particles. DLS tests in this study indicated that the mean size of 99.9% (by number) of the fresh CMC-stabilized ZVI nanoparticles (prepared at 1 g/L and stabilized with 0.9% CMC) was 13.7 ± 2.3 nm (three measurements).…”
Section: Dls Characterization Of Cmc-stabilized Zvi Nanoparticlesmentioning
confidence: 95%
“…More recently, He and Zhao (2007a) demonstrated that the ZVI particle size could be manipulated by applying stabilizers of various molecular weights or by tuning the stabilizer-to-ZVI molar ratio. The stabilized nanoparticles displayed both superior physical stability and much greater reactivity than their non-stabilized counterparts when used for degradation of chlorinated hydrocarbons (He et al 2007) and perchlorate (Xiong et al 2007). …”
Section: Introductionmentioning
confidence: 99%